Efeito da incorporação de macrófitas aquáticas sobre características químicas de solo degradado - Yamauchi, Alfredo Kohiti Feres [UNESP] (2014)
Anthropogenic activity favored the development of an unbalanced environment, favorable to a wide spread of untamed plant species, which causes a series of environmental and economic interference. The control method mostly used for the removal of those plants is the mechanical, however, a problem on this method is the destiny of great amounts of biomass. So, the aims of this study were to evaluate the biomass incorporation effects of Eichhornia crassipes, Salvinia molesta, Brachiaria subquadripara and Typha latifolia, isolated and combined, and of a composted material on chemical soil characteristics. All macrophyte were collected at Santana reservoir, on Piraí/RJ. Part of the biomass was separated by species, and the rest was subjected for composting. The material was dried, milled and analyzed before incorporation. After a 60 days incubation period a sample from each treatment was analyzed. In the end of the tests the biomass incorporation changed positively the chemical characteristics of the soil. The species which mostly contributed with the improvement on nutrient content were B. subquadripara and T. latifolia, incorporated alone and combined. The chemical characteristics which differed significantly with the composted soil incorporation after 10 t.ha-1 dose and the greatest contribution came with 40 t.ha-1. Based on the obtained results, is concluded that E. crassipes, T. latifólia, S. molesta and B. subquadripara incorporation changed positively the chemical characteristics of the soil, as well as the compound incorporation, improving the fertility of a degraded soil